Nano-Bioceramic Production via Mechano-Chemical Conversion (Ultrasonication) - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2013)
The production of nano-calcium phosphate powders, such as HA (hydroxyapatite), from synthetic chemicals can be expensive and time consuming. The skeleton or shells of sea creatures (e.g. sea urchins, shells, corals) could be an alternative source of materials to produce very fine and even nano-structured calcium phosphate biomaterial powders. Hydrothermal conversion under very high pressures or methods such as hot-plating (chemical) or ultrasonication (mechano-chemical), have been proposed to transform naturally derived CaCO3, e.g. aragonite, into apatite based materials. The aim of the present work was to prepare inexpensive nano-sized HA and TCP bioceramics powders from a local sea snail shells as a possible raw material for HA/TCP bioceramics. Empty shells of a local sea snail (Nassarius hinia reticulatus) from Marmara Sea, Turkey were collected from a beach near Istanbul. The collected shells were ground to a particle size <75 mu m. Thermal analyses (DTA/TGA) were performed to determine the exact CaCO3 content and thermal behavior. The raw powder was suspended in an aqueous media which was placed in an ultrasonic bath. The temperature was set at 80 degrees C for 15min. Then, an equivalent (to CaO content) amount of H3PO4 was added drop by drop very gently into the solution. The reaction continued for 8h, following which the liquid component was evaporated off in an incubator at 100 degrees C for 24h. The dried sediment was collected and heat treated at two different temperatures, 400 and 800 degrees C. The morphology of the powders produced was examined using SEM. The crystalline phases were indentified using X-ray analysis.
Keywords: Local sea snail; ultrasonication; natural nano-bioceramics; hydroxyapatite; MECHANICAL-PROPERTIES; HYDROXYAPATITE COATINGS; BONE; FABRICATION; SCAFFOLDS; DENTIN